Crop diversification, impulsivity, and resilience in Ethiopia. Issue 4 (15th August 2022) - Oh, Hyunjyung; Quinlan, Robert; Yoder, Jonathan
Abstract: A person's characteristics, self‐perception, and subjective assessment of their environment affect economic decisions and outcomes. This paper explores how crop diversification and crop choice among subsistence farmers in Ethiopia are related to self‐perceptions of impulsivity and resilience to crisis. Our examination is based on statistical regression methods applied to a sample of 315 households in the Sidama Region who rely on crops and livestock for a substantial proportion of their real income, and many of whom reported significant crises in the form of crop or livestock loss and health problems or death in the family. Despite widespread recognition of the benefits of crop diversification as a risk management strategy, our results suggest that monoculture tends to be more strongly associated with self‐reported resilience. Moreover, our findings suggest that the interaction of household head's impulsivity and monoculture cropping positively affects self‐perceived resilience when they cultivate high‐risk, high‐return crops.